An adaptive overcurrent relay coordination scheme for weakly meshed distribution networks with distributed generation - Pacis, Michael C.
The recommended response to a fault in a distribution network is to disconnect any distributed generation. This response result into unnecessary power interruption to other zones that are not affected by the fault. Therefore, there is a need to introduce an adaptive protection scheme that would address this problem. This thesis presents an adaptive coordination scheme for medium voltage distribution networks, particularly for weakly meshed distribution systems with the presence of distributed generation. Digital relays equipped with communication capabilities were used in this study because of their ability to support adaptive network protection behavior. The adaptive behavior is achieved by utilizing a central control unit, or a main relay control unit (MRCU) that constantly updates the setting of the relays. If there is a change of state, like a loss of line, the MRCU will send pre-computed relay setting that is applicable to the new state. The adaptive scheme was tested using a 46 Bus weakly meshed Italian medium voltage distribution network (MVDN). Overall, the results shows that the procedure was able to determine all possible sets of sequential pairs, and the corresponding relay settings. The offline computation was able to produce pairings and relay settings both for n-1 and n-2 contingency scenarios.